Benefits of Substituting Sitting with Standing and Walking in Free-Living Conditions for Cardiometabolic Risk Markers, Cognition and Mood in Overweight Adults - Duvivier, Bernard M. F. M.; Schaper, Nicolaas C.; Koster, Annemarie; van Kan, Linh; Peters, Harry P. F.; Adam, Jos J.; Giesbrecht, Timo; Kornips, Esther; Hulsbosch, Martine; Willems, Paul; Hesselink, Matthijs K. C.; Schrauwen, Patrick; et al. (Frontiers in Physiology, 2017)
Background: We investigated whether substituting sitting with standing and self-perceived light walking in free-living conditions would improve cardiometabolic risk factors, mood and cognition in overweight/obese adults. Methods: In a randomized, cross-over study, 24 (m/f: 13/11) sedentary overweight/obese participants (64 ± 7 years, BMI 29 ± 2 kg/m2) followed two activity regimens of each four days in free-living conditions: ‘Sit’: sitting 13.5 h/day, standing 1.4 h/day, self-perceived light-intensity walking 0.7 h/day; for ‘SitLess’ these activities lasted 7.6, 4.0 and 4.3 h/day, respectively. Meals were standardized and physical activity was assessed by accelerometry (activPAL). Insulin sensitivity (expressed as Matsuda-index based on an oral glucose tolerance test), circulating lipids, blood pressure, mood (pleasantness and arousal) and cognition were assessed on the morning after the activity regimens. Quality of life and sleep were assessed on the last day of the activity regimens. Results: We observed that AUC (0-190 min) for insulin decreased by 20% after SitLess vs. Sit (10,125 [656] vs. 12,633 [818]; p=0.006). Insulin sensitivity improved by 16% after SitLess vs. Sit (Matsuda-index, mean [SEM]: 6.45 [0.25] vs. 5.58 [0.25] respectively; p=0.007). Fasting triglycerides, non-HDL-cholesterol and apolipoprotein B decreased by 32%, 7% and 4% respectively, whereas HDL-cholesterol increased by 7% after SitLess vs. Sit (all p<0.01). Diastolic blood pressure was lower after SitLess vs. Sit (p<0.05). Pleasantness (as one marker of mood status) after the oral glucose tolerance test was higher after SitLess vs. Sit (p<0.05). There was no significant difference between regimens for cognition, quality of life and sleep. Conclusions: Reducing sitting time in free-living conditions markedly improved insulin sensitivity, circulating lipids and diastolic blood pressure. Substituting sitting with standing and self-perceived light walking is an effective strategy to improve cardiometabolic risk factors in overweight/obese subjects.